(untitled) (GESTIÓN Y TENDENCIAS, 2023)
The study examines the differentiating characteristics in incentive structures between public and private enterprises. It identifies that factors such as the multiplicity of objectives, the difficulty in comparing performance, the heterogeneity in owner preferences, and the inadequate design of representation mechanisms systematically reduce the power of formal incentive schemes in the public sector. The author argues that fixed salary schemes may be more efficient due to long-term civil service career motivations and the need to mitigate political capture. Finally, the research extends the analysis to public services and non-profit organizations, where shared identity, cultural training, and a sense of mission effectively replace financial performance payments.